Characterization and pharmacokinetic evaluation of microcomposite particles of alpha lipoic acid/hydrogenated colza oil obtained in supercritical carbon dioxide. (15th March 2020) - Honjo, Masatoshi; Yasuhide, Okuhara; Yamada, Masayoshi; Higuchi, Sei; Mishima, Kenji; Sharmin, Tanjina; Aida, Taku Michael; Kato, Takafumi; Misumi, Makoto; Suetsugu, Tadashi; Orii, Hideaki; Irie, Keiichi; et al.
Abstract: The work reported here is an extension of our previous findings in which supercritical composite particles (SCP) of alpha lipoic acid (ALA) masked with hydrogenated colza oil (HCO) named as ALA/HCO/SCP were obtained by the modified particles from gas-saturated solutions (PGSS) process in supercritical carbon dioxide in order to obscure the unpleasant taste and odor of ALA. The masking effect on ALA/HCO/SCP was compared with the widely used mechano-chemically masked formulation of ALA and HCO named as MC-50F. In the present study, ALA/HCO/SCP particles were found to have a significant improvement in regard to bitterness, numbness, and smell compared to ALA bulk powders suggesting they were well coated. The pharmacokinetic parameters for ALA/HCO/SCP and ALA bulk powder gave similar values but were significantly different from those of MC-50F. The amount of ALA absorbed into the body, in the administered ALA/HCO/SCP, was comparable to that absorbed by ALA bulk powder, whereas about half portion of ALA of the MC-50F was not absorbed, because the ALA/HCO/SCP particles were small enough and the particles of MC-50F were relatively large and had smaller specific surface area. Therefore, this study suggested a newly masked candidate may offer functional particles with maintained efficacy.